Canthin-6-one alkaloids from Eurycoma longifolia - Mitsunaga, Katsuyoshi; Koike, Kazuo; Tanaka, Tomoko; Ohkawa, Youko; Kobayashi, Yuko; Sawaguchi, Takako; Ohmoto, Taichi (Phytochemistry (Oxford), 1994)
Five new canthin-6-one alkaloids, 9,10-dimethoxycanthin-6-one, 10-hydroxy-9-methoxycanthin-6-one, 11-hydroxy-10-methoxycanthin-6-one, 5,9-dimethoxycanthin-6-one and 9-methoxy-3-methylcanthin-5,6-dione were isolated from the bark and wood of Eurycoma longifolia, along with six known canthin-6-one alkaloids and two known β-carboline alkaloids. Their structures were determined from spectroscopic data and other chemical evidence.